Pembelajaran Inovatif Abad 21 pada Materi Barisan dan Deret dengan Model Pembelajaran Problem Based Learning di SMK Negeri 1 Adiwerna - Sugimin Sugimin; Muljani Sutji (Cakrawala: Jurnal Pendidikan, 2022)
Innovative learning in the 21st century is activity-oriented to practice essential skills within the framework for 21st century skills, namely life and career skills, innovation and learning skills, and information, media, and ICT skills. Learning today tends to be dominated by teachers, whereas students are passive who only hear and pay attention to the teacher's explanation. Therefore, a learning model is needed that is able to build knowledge and problem-solving skills in students so as to improve student learning outcomes. The use of learning models becomes an important factor to achieve the completion of student learning. One learning model that requires students to be active in problem solving is the Problem Based Learning model. The purpose of this research is to find out the effectiveness of innovative 21st century learning through problem based learning in Barisan and Series Materials at SMK Negeri 1 Adiwerna.